Supporting PBL instruction with teacher video self-analysis and reflection. Issue 1 (1st January 2023) - Horak, Anne K.; Marotta, Jessica; Brusseau, Rebecca; Daly, Kimberley
ABSTRACT: This study explored using video self-analysis as a practice to help teachers identify effective problem-based learning (PBL) instruction and identify areas for their professional growth. Five seventh-grade teachers in the United States who varied in age, gender, ethnicity, and years of experience video-recorded their PBL instruction. Teachers then engaged in a semi-structured reflection protocol. The Modified Metacognitive Coach Checklist (MCC-M) supported teachers in this reflection. Researchers conducted an inductive analysis of the transcripts, which is consistent with the constant comparative method. Data analysis showed positive outcomes in promoting long-term changes in beliefs, pedagogy, and in the lives of diverse students when teachers use a specific model of PBL instruction focused on increasing equity in outcomes, and as a driver for reflective practice using video self-analysis.